Design and load testing of large diameter open-ended driven piles - Brown, D. A.; Thompson, William Robert, 1966- (Synthesis of highway practice ;, 2015)
"TRB's National Cooperative Highway Research Program (NCHRP) Synthesis 478: Design and Load Testing of Large Diameter Open-Ended Driven Piles documents information regarding the current state of practice with respect to the selection, use, design, construction, and quality control of large diameter open-ended driven piles for transportation structures. This report may provide agencies with information to develop guidance and methods for technical guides and design codes, as well as to identify gaps in knowledge to guide future research."--